Experimental formulation of white glass frit - Diaz Gonzales, César Raúl (1999)
A standard sample of white glass frit from Mexico was used to perform the physical and chemical analyzes, the results of which have been taken into account to prepare two experimental formulations of white glass frit from domestic and imported raw materials. Ulexite (U) was used in the first formulation and boric acid (B) in the second. Likewise, a study of the volume of glass frit imports was carried out, as well as the countries of origin. Formulation (B) is the one that presented the best results to the physical and chemical tests to which they were subjected, but which still does not meet the requirements of an imported glass frit. It is recommended to make new formulations that allow obtaining a better quality white glass frit.